Liver Resection Promotes (Regulates) Proinflammatory Cytokines in Patients with Hepatocellular Carcinoma - Farshid Fathi; Behnam Sanei; Mazdak Ganjalikhani Hakemi; Reza F. Saidi; Abbas Rezaei (Canadian Journal of Gastroenterology and Hepatology)
Background. Several animal studies have shown the roles of cytokines in regulating liver regeneration following liver resection (LR), which is a type of surgery designed to remove cancerous tumors from the liver. This study investigated how the expressions and serum levels of some pro- and anti-inflammatory cytokines in patients with hepatocellular carcinoma (HCC) were changed during LR. Methods. Liver tissues from 15 patients with HCC were collected and the levels of interleukin-6 (IL-6), tumor necrosis factor-alpha (TNF-α), IL-1α, IL-1 β, IL-10, and transforming growth factor-beta1 (TGF-β1) were assessed using real-time PCR assay at different times before and after LR. The serum values of TNF-α and IL-6 were also measured by ELISA. Results. After 60 and 90 minutes of LR, IL-6 gene expression was significantly increased P<0.001−0.05. The same trend was also observed in TNF-α expression after 90 minutes of LR P<0.01. No significant changes were observed in the expressions of IL-1α, IL-1β, IL-10, and TGF-β1 before and after LR. In addition, LR had significant effects on TNF-α and IL-6 serum levels P<0.05−0.0001. Conclusion. Our data provided further evidence to reveal that IL-6 and TNF-α cytokines are critical to improve liver regeneration.